2008
DOI: 10.1504/ijsoi.2008.019330
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation and swarm intelligence organisation into an emergency department: a balancing approach across Ant Colony Optimisation

Abstract: Healthcare system must be sensitive to the needs of patient, financially viable and cost-effective. Emergency Department (ED) crowding and rising healthcare costs are perceived as significant issues that are getting worse. In order to respond to the growing number of incoming patients, hospital departments, including emergency rooms, have to re-evaluate their current facilities, procedures and practises from an operations management perspective. In a typical ED, it is important to minimise not only the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Another comprehensive review of simulation modelling studies in emergency departments for normal and disaster conditions can be found in Gul et al [27]. Among 106 reviewed papers, only few studies consider an optimization approach [1,18,22,51,59]. Fruggiero et al [22] uses ant-colony optimization along with a simulation model to optimize the resources in an emergency department.…”
Section: Accident and Emergency Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another comprehensive review of simulation modelling studies in emergency departments for normal and disaster conditions can be found in Gul et al [27]. Among 106 reviewed papers, only few studies consider an optimization approach [1,18,22,51,59]. Fruggiero et al [22] uses ant-colony optimization along with a simulation model to optimize the resources in an emergency department.…”
Section: Accident and Emergency Modellingmentioning
confidence: 99%
“…Among 106 reviewed papers, only few studies consider an optimization approach [1,18,22,51,59]. Fruggiero et al [22] uses ant-colony optimization along with a simulation model to optimize the resources in an emergency department. Weng et al [59], Ibrahim et al [33] and Rico et al [51] use OptQuest, a SO engine [49], to optimize nurse and physician numbers and nurse allocation in an influenza outbreak, respectively.…”
Section: Accident and Emergency Modellingmentioning
confidence: 99%
“…Simulation techniques have mainly been used in the literature for the analysis of healthcare systems. Amongst these techniques, the most frequent modeling methodologies are discrete event simulation [20,33,25,36,19,27,30,31,45,49,51] and system dynamics [26,2]. Simulation techniques do not suffer from the state explosion problem and are a good alternative to state-based techniques, nevertheless the time needed to get a required accuracy is often prohibitive.…”
Section: Related Workmentioning
confidence: 99%
“…Azcarate et al [32] used a metaheuristic and simulation approach to analyze management problems in a healthcare context. Fruggiero et al [33] combined computer simulation and ant colony optimization to optimize patient scheduling while balancing the workload between and within resource types. Baesler and Sepulveda [34] present a multiobjective simulation optimization model for a cancer treatment.…”
Section: -3mentioning
confidence: 99%